PENGEMBANGAN MULTIMEDIA PADA MATA PELAJARAN GEOGRAFI SMA KELAS X SEMESTER II UNTUK TOPIK HIDROSFER - Purwita, Ninja Panju (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Issues relating to the use of media in teaching the availability and use of multimedia. Availability media is lacking, so the teacher used the media to its full potential yet. Optimal utilization of the media yet, teachers still use textbooks in class lessons. For hydrosphere topics, such as lakes and wetlands, need not be defined, but by showing an example image of the object directly, therefore, to recognize and understand these natural objects. The purpose of this study produces multimedia for subject high school geography class X semester (hydrosphere). This product is intended to assist students in learning geography. This product is made in a CD (compact disk) learning. This study is designed to be eight stages are: analysis of the material, media design, media production, product validation by matter experts and media experts, confirmations, product revision, product testing, and product revision. Advice in the development consists of the use and development of advanced products. To use the product, it is suggested teachers can use multimedia in geography learning displayed by the LCD to display largerKeyword: Multimedia, Hydrosphere Multimedia Developing